Kinematic alignment of current TKA implants does not restore the native trochlear anatomy - Rivière,C; Dhaif,F; Shah,H; Ali,A; Auvinet,E; Aframian,A; Cobb,J; Howell,S; Harris,S (Orthopaedics and Traumatology: Surgery and Research, 2018)
INTRODUCTION: Preserving constitutional patellofemoral anatomy, and thus producing physiological patellofemoral kinematics, could prevent patellofemoral complications and improve clinical outcomes after kinematically aligned TKA (KA TKA). Our study aims 1) to compare the native and prosthetic trochleae (planned or implanted), and 2) to estimate the safety of implanting a larger Persona® femoral component size matching the proximal lateral trochlea facet height (flange area) in order to reduce the native articular surfaces understuffing generated by the prosthetic KA trochlea. METHODS: Persona® femoral component 3D model was virtually kinematically aligned on 3D bone-cartilage models of healthy knees by using a conventional KA technique (group 1, 36 models, planned KA TKA) or an alternative KA technique (AT KA TKA) aiming to match the proximal (flange area) lateral facet height (10 models, planned AT KA TKA). Also, 13 postoperative bone-implant (KA Persona®) models were co-registered to the same coordinate geometry as their preoperative bone-cartilage models (group 2 - implanted KA TKA). In-house analysis software was used to compare native and prosthetic trochlea articular surfaces and medio-lateral implant overhangs for every group. RESULTS: The planned and performed prosthetic trochleae were similar and valgus oriented (6.1° and 8.5°, respectively), substantially proximally understuffed compared to the native trochlea. The AT KA TKAs shows a high rate of native trochlea surface overstuffing (70%, 90%, and 100% for lateral facet, groove, medial facet) and mediolateral implant overhang (60%). There was no overstuffing with conventional KA TKAs having their anterior femoral cut flush. CONCLUSION: We found that with both the planned and implanted femoral components, the KA Persona® trochlea was more valgus oriented and understuffed compared to the native trochlear anatomy. In addition, restoring the lateral trochlea facet height by increasing t